Emprendimiento y Empoderamiento de la Mujer Rural en el Municipio de Umbitá (Boyacá) 2020 (2020)
This report is presented within the framework of the research seedbed "Balance of entrepreneurial initiatives for the empowerment of rural women" in the municipality of Úmbita (Boyacá), through an insertion in the community, it is possible to develop an initial diagnosis of the women entrepreneurs, allowing to understand the needs they have in matters of business development, recognition, leadership in their family nucleus, and the main activities to which they are engaged, the purpose of this work is to serve as a tool for future implementations of entrepreneurship plans serving as a guide when knowing the characteristics of women.